PENGEMBANGAN LEMBAR KERJA SISWA BERBASIS INKUIRI TERBIMBING PADA POKOK BAHASAN GERAK PADA BENDA - Gracella Monique Tiara Ningsih; Maria Dewati; Mashudi Alamsyah (Schrodinger Jurnal Ilmiah Mahasiswa Pendidikan Fisika, 2020)
This research is development research that aims to produce valid teaching materials in the form of Guided Inquiry-based Student Worksheets (LKS) in junior high schools. This study is a Research & Development (R&D) research proposed by Thiagarajan (4-D). It consists of 4 development stages, namely Define, Design, Develop, and Disseminate. In this study, the data collected were in the form of student worksheet feasibility data from the validator, namely 2 expert lecturers and a teacher. The results showed that the proportion of feasibility of guided inquiry-based worksheets from material expert validators was 66%, design expert validators were 85%. Based on the research, the development of inquiry-based LKS teaching materials suitable for use in science learning materials on Motion on Objects for class VIII.